Trends in advanced HIV disease, treatment interruption, and viraemia in KwaZulu-Natal, South Africa - Sanele S. Mbeje; Lilishia Gounder; Johan S. van der Molen; Lungile Hobe; Thulani Ngwenya; Mlungisi Khanyile; Kwena Tlhaku; Benjamin Chimukangara; Thokozani Khubone; Yukteshwar Sookrajh; Sharana Mahomed; Jennifer A. Brown; et al. (PLOS Global Public Health, 2026)
Advanced HIV disease (AHD), treatment interruption and viraemia remain key challenges to effectiveness of HIV programmes in South Africa. Understanding the trends of these measures and their variation across geographic regions can inform more targeted and responsive interventions. We conducted a retrospective cohort study using routine, de-identified data from TIER.Net, a national HIV electronic register. We curated data from 116 primary care clinics in eThekwini, uMgungudlovu, and uMkhanyakude Districts in KwaZulu-Natal province. We included people living with HIV aged ≥16 years, who initiated or collected ART between 1 July 2018 and 30 June 2023. We examined trends in the annual clinic-level prevalence of AHD, treatment interruption and viraemia, and mapped these outcomes using inverse distance weighted interpolation restricted to 3 nearest neighbours to preserve local influence. Among 123,473 clients initiating ART with CD4 count measurements, the overall prevalence of AHD ranged between 20.0% and 22.2%. The prevalence of treatment interruptions ranged between 11.3% and 13.2% among the 544,066 clients who had scheduled visits. Of the 446,899 clients who had viral load results, overall viraemia, defined as ≥50 copies/mL, increased from 12.9% to 20.2%, whereas high-level viraemia defined as ≥1000 copies/mL remained stable at approximately 6%. Spatial analyses highlighted geographic disparities in AHD, treatment interruption, and viraemia across and within the districts. The persistence of AHD, treatment interruption and viraemia require further investigation and highlight ongoing challenges for HIV control. The observed spatial variation across and within districts spanning urban, peri-urban and rural settings highlight the need for geographically tailored interventions to improve programmatic effectiveness, particularly in hyper-endemic settings.